Female undergraduate's perceptions of intrusive behavior in 12 countries - Archer, John (2017)
The present study examines young women's (N = 1,734) perceptions of the unacceptability of 47 intrusive activities enacted by men. Female undergraduate psychology students from 12 countries (Armenia, Australia, England, Egypt, Finland, India, Indonesia, Italy, Japan, Portugal, Scotland, Trinidad) indicated which of 47 intrusive activities they considered to be unacceptable. Responses were compared with parasite-stress values, a measure of global gender equality and Hofstede's dimensions of national cultures. There was no unanimous agreement on any of the items, even for those relating to forced sexual violence. Cluster analysis yielded four clusters: “Aggression and surveillance” (most agreement that the constituent items were unacceptable), “Unwanted attention,” “Persistent courtship and impositions,” and “Courtship and information seeking” (least agreement that the constituent items were unacceptable). There were no significant relationships between the “Aggression and surveillance” or “Courtship and information seeking” clusters and the measure of gender equality, Hofstede's dimensions of national cultures or the measure of parasite stress. For the “Unwanted attention” and “Persistent courtship and impositions” clusters, women residing in countries with higher gender inequality and higher parasite-stress were less accepting of behavior associated with uncommitted sexual relations, and women in more individualistic societies with higher levels of gender equality were less accepting of monitoring activities. Culture may take precedence over personal interpretations of the unacceptability of intrusive behavior that is not obviously harmful or benign in nature